Le scienze umane, l'interdisciplinarità, lo specifico pedagogico. Una questione ancora aperta - Antonia Criscenti (Firenze University Press, 2019)
Scientific and critical pedagogy becomes a simple process of socialization attentive to market demands.This contribution attempts the relaunch of a critical pedagogy, as paidetical formation now compromised by the advent of a system that measures education as a capacity for material production and consumption.